Towards precision medicine in generalized anxiety disorder: Review of genetics and pharmaco(epi)genetics. (December 2019) - Tomasi, Julia; Lisoway, Amanda J.; Zai, Clement C.; Harripaul, Ricardo; Müller, Daniel J.; Zai, Gwyneth C.M.; McCabe, Randi E.; Richter, Margaret A.; Kennedy, James L.; Tiwari, Arun K.
Abstract: Generalized anxiety disorder (GAD) is a prevalent and chronic mental disorder that elicits widespread functional impairment. Given the high degree of non-response/partial response among patients with GAD to available pharmacological treatments, there is a strong need for novel approaches that can optimize outcomes, and lead to medications that are safer and more effective. Although investigations have identified interesting targets predicting treatment response through pharmacogenetics (PGx), pharmaco-epigenetics, and neuroimaging methods, these studies are often solitary, not replicated, and carry several limitations. This review provides an overview of the current status of GAD genetics and PGx and presents potential strategies to improve treatment response by combining better phenotyping with PGx and improved analytical methods. These strategies carry the dual benefit of delivering data on biomarkers of treatment response as well as pointing to disease mechanisms through the biology of the markers associated with response. Overall, these efforts can serve to identify clinical, genetic, and epigenetic factors that can be incorporated into a pharmaco(epi)genetic test that may ultimately improve treatment response and reduce the socioeconomic burden of GAD.